Proposing model of handling language for smart home system controlled by voice - Huu, Phat Nguyen; Van, Khanh Tong (Vietnam Journal of Science and Technology, 2020)
Voice interaction control is a useful solution for smart homes. Now it helps bring the house closer to people. In recent years, many smart home-based voice control solutions have been introduced (for example: Google Assistant, Alexa Amazon etc.). However, most of these solutions do not really serve Vietnamese people. In this paper, we study and develop Vietnamese language processing model to apply to smart home system. Specifically, we propose language processing methods and create databases for smart homes. Our main contribution of the paper is the Vietnamese language processing database for smart-home system.